Exploring the roots of local government corruption practices in rural Java: An anthropological analysis - Setiadi Setiadi; Henny Ekawati; Fadlan Habib (Faculty of Social and Political Science, Universitas Airlangga, 2022)
Corruption is a crucial issue in Indonesia, including in the administration of village government. This article aims to explain the roots of corruption seen from an anthropological analysis of corruption. This article describes the factors causing corruption practices in rural Java, i.e., local values in village governance practices. The research was conducted in several villages in Bojonegoro Regency-East Java. The data were collected through a series of participatory observations, in-depth interviews, and searching archives. The informants were divided into three groups, i.e., the village officials, the elite groups who were against the village head, and the neutral group. The findings of this study indicate that the root of corruption in the village is caused by strong local values such as loyalty to the village head from his followers, solid harmony, and the ability for the village head to manifest himself as an ideal leadership. Such values make relational models that are full of pleasantries for the sake of themselves and their groups to perpetuate power. This study concludes that non-values factors that further complicate the financial administration system in the form of supralocal interventions had a wider impact on the worsening of the deviation in budget usage.